The Effect of Transfer Funds on District/Municipality Development Performance in West Java Province Indonesia - Suhyanto, Otong; Juanda, Bambang; Fauzi, Akhmad; Rustiadi, Ernan (International Journal of Economics and Financial Issues, 2021)
Regional autonomy intended to enhance the level of community involvement in the development process, the distribution of development outcomes fairly, and pay more attention to the potential and diversity of the region. The implementation of regional autonomy will further accelerate the achievement of development goals because local governments have the authority to plan programs that are tailored to the needs of the community by taking into account the potential in the area. Development performance is the variable used to measure the results of the development process. This study expects to examine the variables of per capita (GDP) gross regional domestic product with constant prices in 2010, open unemployment rate (%), the poverty rate (%), human development index (HDI), and Gini index. The objectives of the present study, to reveal the effect of intergovernmental transfers on district/municipality development performance in West Java Province, the effect of transfer funds is not directly, but through regional spending. Panel data regression analysis used to analyze the indirect effect of transfer funds on regional development performance. The results show that the general block grants (Dana Alokasi Umum-DAU) is a transfer fund that has the greatest impact on the performance of regional development, while in terms of expenditure, which has the most significant effect on the performance of regional development is education spending followed by spending on goods and services. Keywords: development performance, intergovernmental transfers, panel data regression, regional autonomy. JEL Classifications: C33, H11, H50, H76 DOI: https://doi.org/10.32479/ijefi.9399